Studying the Activity of Tyrazinase, Included in the System of Antioxidant Protection of Wines - Gulmira Irgasheva; Shahboz Sherpulatov (Genius Journals, 2022)
On a global scale, 140 countries produce more than 250 million hectoliters of wine with a total vineyard area of 7.6 million hectares. Spain, China, France rank first, Uzbekistan thirteenth in the world in terms of vineyard area, cultivated on 73 thousand hectares, of which 10 thousand hectares are considered wine grape varieties.
Keywords: Oxidized wines; antioxidants; antioxidant defense systems; peroxidase